Societal Accountability in Latin America - Smulovitz, Catalina Silvia (2000)
In Argentina, the unsolved murder of a teenager triggered social protests that eventually led to the trial and indictment of her assailants and the resignation of a provincial governor. In Brazil, press reports of governmental corruption and public demands for due process led to the 1992 impeachment of President Fernando Collor de Mello. In Colombia, the introduction of a constitutional mechanism for the protection of fundamental rights resulted in more than 200,000 legal actions, including indictments for malfeasance in office and for violations of due process. Nongovernmental organizations (NGOs) like Alianza Cívica in Mexico and Poder Ciudadano in Argentina organized campaigns to monitor elections and the financial assets of elective officials. These cases show new ways in which citizens are exercising control of government in many of Latin America's democracies.